2016
DOI: 10.1016/j.ijrobp.2016.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Target of Rapamycin Inhibition With Rapamycin Mitigates Radiation-Induced Pulmonary Fibrosis in a Murine Model

Abstract: Background Radiation-induced pulmonary fibrosis (RIPF) is a late toxicity of therapeutic radiation. mTOR signaling drives several processes implicated in RIPF, including inflammatory cytokine production, fibroblast proliferation, and epithelial senescence. We sought to determine if mTOR inhibition with rapamycin would mitigate RIPF. Methods/Materials C57BL/6NCr mice received a diet formulated with rapamycin (14 mg/kg food) or control diet two days before and continuing for 16 weeks after exposure to 5 daily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 56 publications
(52 reference statements)
2
49
0
Order By: Relevance
“…In a murine model of radiation-induced fibrosis, type II pneumocyte senescence occurred in a time and dose-dependent fashion following whole thorax irradiation, which was thought to reduce the stem cell compartment 71 . There is a complex set of pro-inflammatory, immunomodulatory and mitogenic cytokines that comprise the secretory profile of senescence (SASP), including TGF-β1, IL-1β, and IL-6 that have implications on RILI 72 , 73 . In a more recent murine study of radiation-induced lung fibrosis, rapamcyin effectively mitigated type II pneumocyte senescence, inflammatory cytokine expression, and collagen production 72 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a murine model of radiation-induced fibrosis, type II pneumocyte senescence occurred in a time and dose-dependent fashion following whole thorax irradiation, which was thought to reduce the stem cell compartment 71 . There is a complex set of pro-inflammatory, immunomodulatory and mitogenic cytokines that comprise the secretory profile of senescence (SASP), including TGF-β1, IL-1β, and IL-6 that have implications on RILI 72 , 73 . In a more recent murine study of radiation-induced lung fibrosis, rapamcyin effectively mitigated type II pneumocyte senescence, inflammatory cytokine expression, and collagen production 72 .…”
Section: Discussionmentioning
confidence: 99%
“…There is a complex set of pro-inflammatory, immunomodulatory and mitogenic cytokines that comprise the secretory profile of senescence (SASP), including TGF-β1, IL-1β, and IL-6 that have implications on RILI 72 , 73 . In a more recent murine study of radiation-induced lung fibrosis, rapamcyin effectively mitigated type II pneumocyte senescence, inflammatory cytokine expression, and collagen production 72 . Further study is warranted to determine whether the enlarged type II pneumocytes in the present study represent cells that have undergone radiation-induced early senescence.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, rapamycin treatment partially protects mice from IPF caused by bleomycin 241 or radiation 244 , as well as from hypoxia-induced PAH 245 . Similarly, the intranasal delivery of a Becn1 -coding lentivirus successfully restores autophagy and limits inflammation in Cftr F508Δ mice (a model of cystic fibrosis) 243 , as does the genetic inactivation of Rptor or Mtor in mouse models of hyperoxia-induced or lipopolysaccharide-induced acute lung injury 246,247 .…”
Section: Autophagy As a Therapeutic Targetmentioning
confidence: 99%
“…However, whether mTOR is associated with the regulation of PQ-induced EMT requires further study to confirm. Using a murine model, Chung et al (22) demonstrated that rapamycin treatment reduced inflammatory cytokine expression, extracellular matrix production and senescence in type II pneumocytes, and that rapamycin protected against radiation-induced pulmonary fibrosis. Phosphoinositide 3-kinase (PI3K) was reported as a promising therapeutic target for idiopathic pulmonary fibrosis (23).…”
Section: Discussionmentioning
confidence: 99%